The role of circulating endothelial progenitor cells in the development of vascular retinal diseases - Machalińska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Based on the recent reports, circulating endothelial progenitor cells play an important role in the pathogenesis of vascular-related disorders. It is suggested that ischemia triggers endothelial progenitor cells to proceed from bone marrow into peripheral blood. Consequently, the mobilized endothelial progenitor cells may contribute to neovasculogenesis within injured retina and/or choroid tissue. Hence, in the present review the potential relationship between development of vascular retinal diseases and systemic endothelial progenitor cells migration has been discussed. Understanding of all pathophysiological mechanisms underlying progressive neovascularization may lead to development of effective prevention and treatment of these disorders. Further investigations are required to elucidate precisely the role of endothelial progenitor cells in this process and to create background for therapeutic applications.